Tracing the assembly history of NGC 1395 through its Globular Cluster System - Escudero, Carlos Gabriel (2018)
We used deep Gemini-South/GMOS g'r'i'z' images to study the globular cluster (GC) system of the massive elliptical galaxy NGC1395, located in the Eridanus supergroup. The photometric analysis of the GC candidates reveals a clear colour bimodality distribution, indicating the presence of 'blue' and 'red' GC subpopulations. While a negative radial colour gradient is detected in the projected spatial distribution of the red GCs, the blue GCs display a shallow colour gradient. The blue GCs also display a remarkable shallow and extended surface density profile, suggesting a significant accretion of low-mass satellites in the outer halo of the galaxy. In addition, the slope of the projected spatial distribution of the blue GCs in the outer regions of the galaxy, is similar to that of the X-ray halo emission. Integrating up to 165 kpc the profile of the projected spatial distribution of the GCs, we estimated a total GC population and specific frequency of 6000 ± 1100 and S N = 7.4 ± 1.4, respectively. Regarding NGC1395 itself, the analysis of the deep Gemini/GMOS images shows a low surface brightness umbrella-like structure indicating, at least, one recent merger event. Through relations recently published in the literature, we obtained global parameters, such as M stellar = 9.32 × 10 11 M⊙ and M h = 6.46 × 10 13 M⊙. Using public spectroscopic data, we derive stellar population parameters of the central region of the galaxy by the full spectral fitting technique. We have found that this region seems to be dominated for an old stellar population, in contrast to findings of young stellar populations from the literature.